An Analysis of the Effect of the Implementation of an Integrated Management System (IMS) on Work Ergonomics in an O&M Power Plant Company - Ifadiana, Dewi Permata; Soemirat, Juli (Journal of Engineering and Technological Sciences, 2016)
Ergonomics has developed significantly for the prevention of related accidents. Its implementation, however, depends on the existing management system within a company. The integrated management system (IMS) is frequently implemented in industry, which is an integration of ISO 9001, ISO 14001, and OHSAS 18001. The objectives of this research were to analyze the effects of IMS implementation on work ergonomics and to find the influencing factors. The methods used were the 4x4 method for investigating accidents; interviews; and a questionnaire for workers and managers at an electricity company. The subjects were divided into three levels, namely: top management, middle management, and workers. Logistic regression was used to analyze and estimate the effects of one or more management variables on ergonomics related accidents. The results showed that the implementation of IMS has supported work ergonomics very well based on the average scores, which ranged from 2.99 to 3.38. The logistic regression showed that the most influential IMS on work ergonomics was the Do (D) of Demingâs PDCA cycle, whereas the most influential parameter for ergonomics accident prevention was Policy (P) and Do (D) at the top management level.